2007
DOI: 10.1111/j.1601-183x.2007.00309.x
|View full text |Cite
|
Sign up to set email alerts
|

Perception of sweet taste is important for voluntary alcohol consumption in mice

Abstract: To directly evaluate the association between taste perception and alcohol intake, we used three different mutant mice, each lacking a gene expressed in taste buds and critical to taste transduction: a-gustducin (Gnat3), Tas1r3 or Trpm5. Null mutant mice lacking any of these three genes showed lower preference score for alcohol and consumed less alcohol in a two-bottle choice test, as compared with wild-type littermates. These null mice also showed lower preference score for saccharin solutions than did wild-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
55
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 76 publications
5
55
0
Order By: Relevance
“…It is suggested that the ability of ethanol to stimulate neural pathways involved in the transduction of sweet taste (Hellekant et al 1997;Lemon et al 2004) plays an important role in its consumption (Blednov et al 2008). Consistent with this, genetic deletion of T1R3 and its associated G protein subunit (␣-gustducin) or the downstream nonspecific cation channel (TRPM5) significantly decreases alcohol preference in KO mice (Ellingson et al 2009).…”
Section: Alcohol Preference and Sweet Tastementioning
confidence: 81%
See 1 more Smart Citation
“…It is suggested that the ability of ethanol to stimulate neural pathways involved in the transduction of sweet taste (Hellekant et al 1997;Lemon et al 2004) plays an important role in its consumption (Blednov et al 2008). Consistent with this, genetic deletion of T1R3 and its associated G protein subunit (␣-gustducin) or the downstream nonspecific cation channel (TRPM5) significantly decreases alcohol preference in KO mice (Ellingson et al 2009).…”
Section: Alcohol Preference and Sweet Tastementioning
confidence: 81%
“…Differences in sensitivity to or preference for salty taste have been reported in subjects with a paternal history of alcohol dependence relative to control subjects with no paternal history (Scinska et al 2001). A positive association exists between ethanol intake and sweet taste (Stewart et al 1994;Woods et al 2003) involving the gene for T1R3 (Bachmanov et al 2001(Bachmanov et al , 2002Blednov and Harris 2007;Blednov et al 2008;Blizard 2007;Brasser et al 2010;Inoue et al 2004;Lu et al 2005;Nelson et al 2001), a G protein-coupled receptor (GPCR) that combines with another GPCR (T1R2) to function as the broadly tuned, heterodimeric, sweet taste receptor T1R2ϩT1R3 Zhao et al 2003). Alcohol dependence and use also show significant association with the T2R38 gene, a marker for 6-n-propylthiouracil bitterness, and with hT2R16, a gene encoding a taste receptor for the bitter-tasting ␤-glucopyranosides (Duffy et al 2004;Hinrichs et al 2006).…”
mentioning
confidence: 99%
“…In fact, their 0.2% saccharin preference declined from initial test (before saccharide tests) to test 3, and the KO mice strongly avoided 0.8% saccharin in test 3. Saccharin avoidance by KO mice has been attributed to the mice responding to the bitter taste component of the artificial sweetener (5). The saccharin avoidance by the KO mice in the last test clearly demonstrates that their sucrose preference in the second test does not represent a recovery of sweet taste sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Prior genetic mapping studies in mice have revealed a common chromosomal locus contributing to alcohol and sweetener consumption (the Ap3q alcohol preference/Sac locus; Bachmanov et al 2002) Nelson et al 2001;Sainz et al 2001;Zhao et al 2003). Knockout mice lacking the T1r3 receptor display substantially reduced intake of and preference for alcohol and sweet stimuli, but normal intake of other tastants, relative to B6 wild-type mice (Blednov et al 2008;Brasser et al 2010). Moreover, central taste-sensitive neurons in T1r3 receptordeficient mice show suppressed electrophysiological responses to oral ethanol and sweet stimuli, but not other tastants, relative to B6 control animals (Brasser et al 2010).…”
mentioning
confidence: 99%